Tacrolimus-Induced Type IV Renal Tubular Acidosis following Liver Transplantation - Schmoyer, Christopher (Case Reports Hepatol, 2017)
Calcineurin inhibitors remain an integral component of immunosuppressive therapy regimens following solid organ transplantation. Although nephrotoxicity associated with these agents is well documented, type IV renal tubular acidosis is a rare and potentially underreported complication following liver transplantation. Hepatologists must be able to recognize this adverse effect as it can lead to fatal hyperkalemia. We describe a case of tacrolimus-induced hyperkalemic type IV renal tubular acidosis in a patient following an orthotopic liver transplant for alcoholic cirrhosis.